Assessment of Antioxidant and Cytotoxicity Activities of Saponin and Crude Extracts of Chlorophytum borivilianum. (2nd October 2013) - Ashraf, Mehdi Farshad; Abd Aziz, Maheran; Stanslas, Johnson; Ismail, Ismanizan; Abdul Kadir, Mihdzar
Abstract : The present paper focused on antioxidant and cytotoxicity assessment of crude and total saponin fraction of Chlorophytum borivilianum as an important medicinal plant. In this study, three different antioxidant activities (2, 2-diphenyl-1-picrylhydrazyl radical scavenging (DPPH), ferrous ion chelating (FIC), and β -carotene bleaching (BCB) activity) of crude extract and total saponin fraction of C. borivilianum tubers were performed. Crude extract was found to possess higher free radical scavenging activity (ascorbic acid equivalents 2578 ± 111 mg AA/100 g) and bleaching activity (IC50 = 0.7 mg mL −1 ), while total saponin fraction displayed higher ferrous ion chelating (EC50 = 1 mg mL −1 ). Cytotoxicity evaluation of crude extract and total saponin fraction against MCF-7, PC3, and HCT-116 cancer cell lines using 3-(4, 5-dimethylthiazol-2-yl)-2, 5 diphenyltetrazolium bromide (MTT) cell viability assay indicated a higher cytotoxicity activity of the crude extract than the total saponin fraction on all cell lines, being most effective and selective on MCF-7 human breast cancer cell line.